Presenças do corpo e do inconsciente em ambientes digitais - do Carmo Cardoso Sampaio, Maria (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Since the Greek my thof Narcissus to the figures that permeate the digital environments, the question sof the body and unconscious calls for theories support from Freud to Lacan, since the lacanian idea of imago and the visual image, will redeem freudiana in classic al theory, the term narcissism, nottoconnote any investment of the ego, but to connote the investment to fan image of the ego. Image which assumes see and be seen. In this sense, the excessive number of posting photos of the same user on facebook is highlighted as empirical example because, in the lacanian theory, this excess imagos serves to protect the individual against the risk entropy. It has a marked defensive role and at the same time it is evolving.
Keywords: Body; Unconscious; Digital; Psychoanalysis